The new paradigm for wireless network optimization a synergy of automated processes and human intervention. - Hampel, Georg
With the evolution of wireless technologies, the optimization process for the radio access network has undergone a dramatic increase in complexity. This trend is driven by the introduction of multiple objectives for packet data services, the increasing network heterogeneity resulting from technology overlays, and the growing demand for nondisruptive optimization of operating networks. In a multidisciplinary effort, Bell Laboratories has developed a new optimization methodology that tackles these challenges using automated processes. We show that the paradigm shift toward automation requires the development of several interdependent algorithms each designed to cope with a particular optimization task. In the application described, human intervention proves indispensable; it demands a new kind of expertise that combines understanding of the automated processes with knowledge of network operation. Through examples we illustrate the variety of tasks that have to be automated and where guidance is needed through human control. The development of these automated processes is an important step toward dynamic optimization routines that are integrated into the network and adjust the network in a real-time manner.
Keywords: Automated process; Human intervention; Packet data service; Radio access network; Wireless network optimization